The Relationship between Definitional Skills and Listening Comprehension: Preliminary Evidence from Preschoolers to School-Aged Children - Катерина Артусо; Elena Torelli; Carmen Belacchi (Journal of Language and Education)
Background: Definitional skills represent the ability to express words’ meaning using canonical formats (i.e., ‘a cat is a domestic animal that meows’). This complex linguistic production requires lexical, semantic, morphosyntactic, pragmatic and metalinguistic abilities, all implicitly mastered in language listening comprehension. Listening comprehension has a crucial role also in the cognitive linguistic mediated development, especially in promoting future reading comprehension. The relationship between definitional skills and listening comprehension is an underinvestigated topic.